Suburbs around the Czech provincial city of České Budějovice – territorial arrangement and problems - Kubeš, Jan; Nováček, Aleš (Hungarian Geographical Bulletin, 2019)
The article is a contribution to discussions about the territorial arrangement of suburbs, their types and other settlements in suburban zones around post-socialist CEE provincial cities, based on the example of the South Bohemian “one-hundred-thousand” city of České Budějovice, including territorial development problems of suburbs and other settlements. Suburbs, separated from the city by free space, originate there from the original villages. These suburbs are population-growing settlements with the majority of flats in newer houses, immigrants from the city and economically active people working in the city (based on census data and ongoing registrations). Nearby, moderately distant and more distant suburbs occur in three concentric suburban sub-zones around the examined city, in which the population and spatial size of the suburbs gradually diminish. Semi-suburbs with partial suburbanisation and small towns also occur there. The territorial development problems of some suburbs are mainly associated with the disordered (sub)urban sprawl, the inadequate architecture of new houses, the poor quality and capacity of the technical infrastructure, the lack of public transport connections to the city, the absence and low capacity of kindergartens and elementary schools, clashes with recreational second homes, the lack of greenery and the losses of agricultural land.